Re-imagining Pedagogy for Early Childhood Education Pre-service Curriculum in the Face of the COVID 19 Pandemic - Mphahlele, Ramashego; Jikpamu, Bethia Tanneh (Journal of Interdisciplinary Studies in Education, 2021)
COVID-19 has caused a change in the demography of the Early Childhood Education (ECE) teaching fraternity. This paper problematizes the ECE curriculum delivery gap created by the influence of COVID-19. Central to this paper is the assumption that online learning might limit the stimulation of children’s holistic development. Reflecting on their experiences, the authors examine the influence of COVID-19 on pedagogy for ECE pre-service and kindergarten curriculum through the lens of design thinking theory. The reflections are based on one open and distance learning institution in South Africa and one kindergarten program in Canada. The findings reveal challenges, such as digital inequality brought on by socio-economic imbalances and opportunities. The authors suggest the digital literacy skills needed to mitigate the influence of COVID-19 in the ECE pre-service and kindergarten curriculum delivery.